2016
DOI: 10.7554/elife.13308
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling is a potent regulator of liver lipid metabolism and reveals a GLI-code associated with steatosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in industrialized countries and is increasing in prevalence. The pathomechanisms, however, are poorly understood. This study assessed the unexpected role of the Hedgehog pathway in adult liver lipid metabolism. Using transgenic mice with conditional hepatocyte-specific deletion of Smoothened in adult mice, we showed that hepatocellular inhibition of Hedgehog signaling leads to steatosis by altering the abundance of the transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 73 publications
8
65
0
Order By: Relevance
“…This is in agreement with our observation in HPE patients— most of whom are not overweight—and suggests a new mechanism of NAFLD manifestation. These findings are in concert with the recent work of Matz-Soja et al [12] showing that conditional hepatocyte-specific deletion of Smoothened (a Patched-inhibited Hh co-receptor) in adult mice produces liver steatosis independent of insulin resistance. Previous studies have indicated that Hh signaling defects stimulate systemic adipogenesis [11, 34, 35], which can lead to metabolic complications such as dyslipidemia, type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is in agreement with our observation in HPE patients— most of whom are not overweight—and suggests a new mechanism of NAFLD manifestation. These findings are in concert with the recent work of Matz-Soja et al [12] showing that conditional hepatocyte-specific deletion of Smoothened (a Patched-inhibited Hh co-receptor) in adult mice produces liver steatosis independent of insulin resistance. Previous studies have indicated that Hh signaling defects stimulate systemic adipogenesis [11, 34, 35], which can lead to metabolic complications such as dyslipidemia, type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have proposed that increased PPARγ expression promotes liver steatosis and have attributed a causal role to PPARγ through mechanisms involving activation of lipogenic genes and de novo lipogenesis [12, 31]. Furthermore, it has been demonstrated that PPARγ inhibits monocyte and macrophage inflammatory responses and prevents myofibroblastic transdifferentiation of HSC [31], which explains the reduced expression or lack of induction of fibrosis markers and pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse liver displayed a perivenous zonation of IHh [164] and conditional hepatocyte-specific deletion of SMO resulted in periportal lipid accumulation and up-regulation of key lipogenic transcription factors such as SREBP and PPARs and enzymes such as FASN [165]. The latter displayed a reversed zonation in the SMO deleted mice; instead of being perivenous [8], [166] like in the control mice, FASN was detected in the periportal zone of the SMO knockouts.…”
Section: Hedgehog Signalingmentioning
confidence: 96%
“…The steatogenic effect of Gli suppression resulted from a skewing of lipid metabolism towards lipogenesis through the induction of lipogenic factors such as sterol regulatory element-binding protein (SREBP)-1c and adiponutrin/patatin-like phospholipase domain-containing protein-3 (PNPLA-3). Furthermore, activation of the Hh pathway (through SUFU knockdown, small molecule Shh agonists or Gli overexpression) reversed the steatogenic phenotype in hepatocytes derived from genetic models of obesity-related NAFLD, i.e., ob/ob mice and melanocortin-4 knockout mice (Matz-Soja et al, 2016). …”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%